(untitled) (London, UK, 2004)
"Innovations" is a new five-level general English course for classes looking for new material with a fresh approach. Based on a language-rich, lexical/grammatical syllabus, it starts from the kinds of natural conversations that learners want to have
Keywords: English language,English language; Study and teaching